Non-material costs of wildlife conservation to local people and their implications for conservation interventions. (June 2020) - Thondhlana, Gladman; Redpath, Stephen Mark; Vedeld, Pål Olav; van Eeden, Lily; Pascual, Unai; Sherren, Kate; Murata, Chenai
Abstract: In assessment of costs (and benefits) of wildlife conservation, conventional economic valuation frameworks may inadequately address various non-tangible values and neglect social, cultural and political contexts of resources and their use. Correspondingly, there seems to be much more focus on quantifying the economic, material benefits and costs of wildlife conservation than the non-material aspects that also affect human well-being. In addition, current research on the costs of wildlife conservation tends to be discipline-focused which constrains comparability, often causing conceptual ambiguity. This paper is an attempt to address this ambiguity. While there is growing acknowledgement of the material costs of wildlife conservation, we contend that employing a broader, composite social well-being approach may provide better conceptual insights on—and practical options for—managing various non-material impacts of wildlife conservation for local people. Non-material impacts such as negative physical or psychological experiences, trauma, feelings of fear and anxiety cannot directly be measured by or converted to money but such impacts still lead to human ill-being. Thus, taking these impacts into account is critical for the broader sustainability of wildlife conservation, making understanding and addressing them a key socio-ecological issue. Highlights: Current research on the costs of wildlife conservation tends to focus on material aspect of human well-being. Limited studies on non-material costs are characterised by conceptual ambiguity, which limits comparability. A better understanding of non-material costs of wildlife conservation can improve wildlife conservation. We define, categorizeand characterize non-material costs of wildlife conservation. Implications for measuring non-material costs and designing socially just conservation interventions are discussed.